Y' = 6x + 18
6x + 18 = 0
6x = -18
x = -3
y(-3) = 3(-3)^2 + 18*(-3) - 7 = 27 - 54 - 7 = -34
y(-5) = 3*(-5)^2 + 18*(-5) - 7 = -75 - 90 - 7 = -172
y(0) = 3*(0)^2 + 18*(0) - 7 = -7
наибольшее -7
наименьшее -172
==========
y' = 3x^2-12x-15
3x^2 - 12x - 15 = 0
x^2 - 4x - 5 = 0
D = 16 - 4*1*(-5) = 36
x1 = (4+6)/2 = 5
x2 = -1 - не принадлежит [-1/2; 6]
y(-1) = (5)^3 - 6*5^2 - 15*5 - 2 = 125 - 150 - 75 - 2 = -102
y(-1/2) = (-1/2)^3 - 6*(-1/2)^2 - 15*(-1/2) - 2 = 1/8 - 3/2 +15/2 - 2 = 1/8 + 6 - 2 = 4 + 1/8 = 33/8 = 4.125
y(6) = (6)^3 - 6*6^2 - 15*6 - 2 = 216 - 216 - 90 - 2 = -92
наибольшее 4.125
наименьшее -102